Changes in Water Soluble Protein Profile of Antarctic Cyanobacterium Nostoc Commune under Temperature Downshift from 25° to 5 °C. Issue 3 (16th March 2019) - Tripathi, Ranjana; Rai, Pradeep Kumar; Rai, Anuradha; Singh, Surendra
Abstract: The cyanobacterium Nostoc commune (Nostocales) is an isolate from the Schirmacher Oasis Antarctica. The cyanobacterium is psychrotropic in nature; and maintained in laboratory at 25 °C temperature, in unialgal form. Here, we studied the change in protein profile of water soluble proteins from exponentially growing N. commune upon downshift from its optimum growth temperature (25 °C) to a low temperature (5 °C). Experimental set up used to analyze the proteome were- a sudden shift to low temperature (i.e., cold shock), after short- (8 days) and long-term acclimation (7 weeks) to low temperature (5 °C). Cold-shock resulted in an increase in Low molecular weight proteins (LMWPs) with clouding of diffused proteins. Further increase in the duration of incubation period (short- and long-term acclimation) caused dissociation of proteins, indicated by NaCl (50–600mM) induced dissociation of proteins. That is, high molecular weight proteins (HMWPs) dissociated into LMWPs resulting in an increased number of protein bands. This was further confirmed by addition of LMWPs (≤10KDa) resulting in re-association of proteins into HMWPs. Hence, we report that the cold-induced synthesis of LMWPs (≤10kDa) is a strategy adopted by the N. commune to survive at low temperature of Antarctica.